A clinical study on pityriasis rosea - Egwin Anand; Martis Jacintha; Bhat Ramesh; Kamath Ganesh; Nanda Kishore (Wolters Kluwer Medknow Publications, 2005)
Pityriasis rosea is an acute inflammatory dermatosis of unknown etiology with a self-limited course. Fifty patients of pityriasis rosea attending out patient department of our hospital were selected for the study and the data was analysed. In the present study out of 50 cases, 30(60%)were males and 20(40%)were females, giving male: female ratio 1.5:1. Majority of the patients 16(32%) were seen in the age group of 11-20 years. Precipitating factors include wearing new garments in 10(20%) patients, drugs in 5(10%) and both new garment and drug in 1(2%) patient. Thirty five (70%) patients presented with herald patch and the distributions of secondary eruptions were mainly on the trunk among 47(94%) patients. Classical pityriasis rosea (62%) was the commonest morphologic type, followed by atypical pityriasis rosea (38%) which include absence of herald patch (30%), localized pityriasis rosea (4%) and inverse pityriasis rosea and papulo -vesicular pityriasis rosea (2%) each.